Implementation of the ASEAN Political-Security Community (APSC) Blueprint by Indonesia in Handling Rohi Ngya Refugees in Aceh (Community Security Perspective) - Atin, Auliya; Hadiwijoyo, Surya Sakti; Simanjuntak, Triesanto Romulo (Jurnal Indonesia Sosial Sains, 2024)
The ongoing humanitarian crisis faced by Rohingya refugees has drawn significant attention across Southeast Asia, particularly regarding Indonesia’s response under the ASEAN Political-Security Community (APSC) Blueprint. This study aims to analyze Indonesia's implementation of APSC policies in handling Rohingya refugees in Aceh, focusing on the balance between community security and humanitarian obligations. Using a qualitative approach, this research employs a case study method, analyzing data from policy reports, official documents, and community feedback. The findings indicate that while Indonesia has made efforts to assist refugees, challenges persist due to limited legal frameworks and mixed local reception. The study reveals that community security concerns, alongside the lack of comprehensive refugee policies, have led to social tensions in Aceh, impacting both the refugee population and the host community. The research concludes that to enhance the effectiveness of APSC policies, Indonesia must foster greater community engagement and optimize resource allocation, thus promoting a more stable environment for both refugees and local residents.